Deadline in Rome - "Call, Max." ("Lincoln, Va. : Chosen Books ; Waco, Texas :")
CHRISTIAN FICTION. LCSH
Keywords: "PHOEBE (BIBLICAL FIGURE) -- FICTION.;PAUL, THE APOSTLE, SAINT -- FICTION.;BIBLE. N.T. -- HISTORY OF BIBLICAL EVENTS --;FICTION.;CHURCH HISTORY -- PRIMITIVE AND EARLY CHURCH, CA.;30-600 -- FICTION.;CHRISTIAN SAINTS -- FICTION.;ROME (ITALY) -- FICTION.;APOSTLES -- FICTION.;BIOGRAPHICAL FICTION. GSAFD"